Stabilization of a light bullet in a layered Kerr medium with sign-changing nonlinearity - Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2004)
The stabilization of light bullets in a layered Kerr medium with sign-changing nonlinearity along the propagation direction was discussed. It was found that an oscillating Kerr nonlinearity produced a minimum in the effective potential. Light bullet with large power was collapsed slowly by the stabilized soliton. It is shows that the oscillating Kerr nonlinearity stops the collapse and enhances the lifetime of the soliton.